Ratings, qualidade creditícia e estrutura de capital em países emergentes - Homrich, Pedro Oliveira (2023)
The companies' access to credit is a relevant factor to enable investments and the development of companies. In this sense, instruments for measuring the ability of companies to honor their debts are crucial for creditors, which is why credit ratings emerge as a pertinent measurement of the creditworthiness of companies, centralized by rating agencies, rather than to be evaluated individually by each creditor agent. The rating of countries (Sovereign Rating) also reflects the economic situation of a given country, consequently impacting the performance of domestic companies. In this sense, this research studied the interaction between the credit ratings of firms in emerging countries, the sovereign rating of these countries and variables of credit quality and capital structure of these firms, verifying if firms with a rating equal to or greater than the sovereign are impacted by a swing in the sovereign rating (the “sovereign ceiling effect”). The interactions between credit rating and Long-Term Debt, Debt/EBITDA, Total Debt, among others, were also studied. Data from 2000 to 2021 were collected from 16 emerging countries. Using the Dynamic Diff-in-Diff methodology with Kernel Propensity Score Matching (PSM), it was found that the effect of a sovereign downgrade is asymmetric between companies, but different from what occurs in the study of some authors , in this research, the reduction is smaller for companies rated above or equal to the sovereign. The effect on the Debt/EBITDA was also different from what was expected, and other significant variables were consistent with what was presented in other studies. This dissertation and the presented results converge to the fact that even though several authors have found similar results regarding the interactions between sovereign and credit ratings, there are still numerous points to be researched more deeply, especially regarding the contrast between the reality of developed and emerging countries